Toxicity of carboxylated carbon nanotubes in endothelial cells is attenuated by stimulation of the autophagic flux with the release of nanomaterial in autophagic vesicles - Orecna, Martina; De Paoli, Silvia H; Janouskova, Olga; Tegegn, Tseday Z; Filipova, Marcela; Bonevich, John E; Holada, Karel; Simak, Jan (Nanomedicine, 2014)
UNLABELLED: Carbon nanotubes (CNTs) exhibit a number of unique properties that make them attractive for various nanomedicine applications including their intravascular use. Therefore, the vascular toxicity of CNTs is a critical safety concern and methods of CNTs toxicity modulation are of great interest. Here, we report that carboxylated multiwalled carbon nanotubes (MWCNTs) induce a decrease in viability of cultured human umbilical vein endothelial cells (HUVECs) associated with the profound accumulation of autophagosomes. This autophagosome accumulation was mTOR kinase independent and was caused by blockade of the autophagic flux rather than by activation of autophagy. Stimulation of the autophagic flux with 1nmol/L bafilomycin A1 attenuated the cytotoxicity of carboxylated MWCNTs in HUVECs and was associated with the extracellular release of the nanomaterial in autophagic microvesicles. Thus, pharmacological stimulation of the autophagic flux may represent a new method of cytoprotection against toxic effects of nanomaterials. FROM THE CLINICAL EDITOR: This study investigates the mechanisms of toxicity of multiwalled carbon nanutubes on human endothelial cells, concluding that pharmacological stimulation of autophagic flux may represent a new method of cytoprotection against the toxic effects of these nanomaterials.
Keywords: nanostruktury; Autophagy; Nanotubes, Carbon; Human Umbilical Vein Endothelial Cells; nanotrubičky uhlíkové; Macrolides; lidé; Microvesicles; makrolidy; Endothelial Cells; Exocytosis; autofagie; exocytóza; endoteliální buňky; Bafilomycin A1; Carbon nanotubes; endoteliální buňky pupečníkové žíly (lidské); Nanostructures; Humans